Stochastic modeling of multiwavelength variability of the classical BL Lac object OJ 287 on timescales ranging from decades to hours - Goyal, Arti; Sadegi, Sepideh (Arxiv, 2018)
We present the results of our power spectral density analysis for the BL Lac object OJ\,287, utilizing the {\it Fermi}-LAT survey at high-energy $γ$-rays, {\it Swift}-XRT in X-rays, several ground-based telescopes and the {\it Kepler} satellite in the optical, and radio telescopes at GHz frequencies. The light curves are modeled in terms of continuous-time auto-regressive moving average (CARMA) processes. Owing to the inclusion of the {\it Kepler} data, we were able to construct for the first time the optical variability power spectrum of a blazar without any gaps across $\sim6$ dex in temporal frequencies. Our analysis reveals that the radio power spectra are of a colored-noise type on timescales ranging from tens of years down to months, with no evidence for breaks or other spectral features. The overall optical power spectrum is also consistent with a colored noise on the variability timescales ranging from 117 years down to hours, with no hints of any quasi-periodic oscillations. The X-ray power spectrum resembles the radio and optical power spectra on the analogous timescales ranging from tens of years down to months. Finally, the $γ$-ray power spectrum is noticeably different from the radio, optical, and X-ray power spectra of the source: we have detected a characteristic relaxation timescale in the {\it Fermi}-LAT data, corresponding to $\sim 150$\,days, such that on timescales longer than this, the power spectrum is consistent with uncorrelated (white) noise, while on shorter variability timescales there is correlated (colored) noise.
Gesehen am 01.02.2019